The Meq Gene Molecular Profile of Marek’s Disease Virus Serotype 1 From Kampung and Arabic Chicken Farms in Sukabumi, West Java, Indonesia - Risza Hartawan; Ni Luh Putu Indi Dharmayanti (Bogor Agricultural University, Indonesia, 2016)
There is an increasing trend to use molecular approaches to the study of Marek’s disease virus serotype 1 (MDV-1), the causative agent for the neoplastic syndrome of chickens known as Marek’s disease. The meq gene is of particular interest as it is the principal oncogene of the virus. This study aimed to characterize the meq gene of field strains of MDV-1 circulating in Kampung and Arabic chicken farms in Sukabumi, West Java, Indonesia during 2014. This study detected circulating MDV-1 strains in Kampung chickens in extracts from feather, blood and dust samples. In comparison only the MDV-1 vaccine strain CVI988/Rispens was identified in Arabic chickens in feather samples. Although the MDV-1 field strain, SMI14-KampungCk was detected in healthy Kampung chicken. Its meq gene is identical with Marek’s disease virus causing outbreak in layer farms in North Sumatera in 2013. Our result shows that the meq gene of Marek’s virus field strain from Sukabumi has the closest proximity with G2, a very virulent Marek’s disease virus from China. The molecular analyses of the meq gene indicated that SMI14-KampungCk has pathotype trait of virulent or very virulent.